Determinants of extinction in a streamed trial procedure. Issue 5 (May 2023) - Witnauer, James E; Castiello, Santiago; Fung, Ethan; Pitliya, Riddhi J.; Murphy, Robin A; Miller, Ralph R
The strength of an association between a cue and its outcome is influenced by both the probability of the outcome given the cue and the probability of the outcome in the absence of the cue. Once an association has been formed, extinction is the procedure for reducing responding indicative of the association by repeated presentation of the cue without the outcome. The present experiments tested whether cumulative frequency and/or cumulative duration of these events affects associative extinction in a streamed trial extinction procedure with human participants. Experiment 1 assessed the effects of parametric manipulations of the frequency and duration of either the cue by itself or cue–outcome co-absence. In Experiment 1, participants proved relatively insensitive to manipulation of the event's duration. In contrast, judgements of the association by participants decreased when the frequency of cue-alone events was increased, even when the durations of those events were decreased so that cumulative exposure to the cue was equated. No effect of either the duration or the frequency of cue–outcome co-absence was observed. Experiment 2 demonstrated that the effect of cue-alone (i.e., extinction trial) frequency generalises across a wide range of parameters for initial acquisition achieved by cue–outcome pairings. Experiment 3 tested for an interaction between event duration during initial learning and event duration during extinction. Collectively, these results indicate that the cumulative frequency, and not the cumulative duration, of extinction trials as well as the duration of the cue–outcome co-absences between extinction trials control the effectiveness of an extinction procedure.